Diagnosis, treatment, and management of Mpox in urban Informal Settlements in Southwestern Nigeria: an ethnographic approach - Olufunke Adegoke; Megan Schmidt-Sane; Michael Kunnuji; Syed Abbas; Akanni Lawanson; Ayodele Jegede; Hayley MacGregor (BMC Public Health)
Abstract Background Global re-emergence of the zoonotic viral disease, Mpox (Monkeypox) has drawn global attention, leading to its declaration as a Public Health Emergency of International Concern (PHEIC) by World Health Organisation (WHO) in July 2022. Nigeria is a spotlight identified for the viral disease outbreak, with attention drawn on its transmission to non-endemic nations. With the country’s healthcare challenges, care seeking practices particularly amongst low-income urban informal settlement populations are diverse – presenting challenges to both case identification and management during an outbreak. In this study, we examine the social, economic, and behavioural context of Mpox therapeutics. Methods This was an ethnographic study conducted between September 2022 and March 2023, with the purposive selection of urban informal settlements and interlocutors in Oyo, Ogun and Lagos States. We interviewed a total of 28 interlocutors who were either confirmed or suspected cases of Mpox or parents of children who are confirmed or suspected Mpox cases identified by the public health workers. Data were elicited through In-depth interviews and observations technique on the interlocutor’s local knowledge and their lived experiences on the therapeutics of Mpox. Analysis of the transcript was done inductively using thematic analysis process. Findings The study revealed awareness and vague knowledge of Mpox. Furthermore, the behavioural practices on how ailments are understood and managed revealed a commonality in their social actions in terms of local diagnosis and management. Mpox was perceived to be a mild disease, and this had implications on the local characteristics of the PHEIC in the endemic regions. Conclusion Our paper contributes to a more nuanced understanding of not only the health care access barriers, but the complex geographical, economic, and sociocultural factors that shape how and when people seek care for Mpox within the context of urban informal settlements. This further draws attention to behavioral dispositions to the nomenclature of what is perceived as PHEIC. Thus, the global health and security paradigm should give room to local context, expertise, and global politics in shaping epidemic responses.